Implementation of regulatory impact and regulatory function of the law in modern Russia - Eldarovna Adygezalova, Gyulnaz; Alekseevich Zhinkin, Sergey; Valerievna Faroi, Tatyana; Nikolaevna Zhbyr, Oksana; Stanislavovna Kich, Irina (Opción, 2019)
The article examines some theoretical issues related to the implementation of the regulatory impact of the law. In this context, it is impossible to underestimate the value impact on an individual, their worldview, system of ideals, and a number of other aspects. The aim of this work is to study the regulatory function of the law, in- cluding its value content. A complex of general scientific methods was used in the course of the study, including historical, comparative, and logical (including ab- straction). The study showed that the regulation of relations in society is the main purpose of the law. Its implementation is possible only if the norms of the law (by determining the legal status of subjects of law, as well as giving life circumstances the status of legal facts) take into account the value orientation of a person and the moral and ethical principles that can serve as a motive for legitimate behavior. The novelty of this study is related to the fact that an attempt is made to determine the stages of the regulatory impact of the law. The law is considered through the prism of its regulatory function, taking into account the values supported in society.